Proportion of extended-spectrum ß-lactamase-producing Enterobacteriaceae in community setting in Ngaoundere, Cameroon - Lonchel Carine; Meex Cécile; Gangoué-Piéboji Joseph; Boreux Raphaël; Assoumou Marie-Claire; Melin Pierrette; De Mol Patrick (BMC Infectious Diseases, 2012)
Abstract Background There is no information regarding the resistance mechanisms of extended-spectrum ß-lactamase (ESBL)-producing Enterobacteriaceae in community setting in Cameroon. The current study aimed to determine the proportion of ESBLs in Enterobacteriaceae isolated in the community and to analyse some risk factors associated with ESBL carriage. Methods Faecal samples were collected from 208 different outpatients and 150 healthy student volunteers between 3 January and 3 April 2009. Enterobacterial isolates resistant to third-generation cephalosporins were screened for ESBL production by the double-disk synergy test. Presumptive ESBL-producing isolates with positive synergy test were identified by Mass Spectrometry using the BioTyper MALDI-TOF. For such ESBL positive isolates, antibiotic susceptibility was determined by the Vitek 2 system. PCR and sequencing were performed for the detection of different types of ESBL genes in presumptive ESBL-producing isolates. Statistical methods were used for the univariate calculation of risk factors. Results During the study period, a total of 358 faecal samples were analysed; 58 of such samples (16%) showed an ESBL phenotype and were confirmed by PCR. The proportion of ESBL producers in faecal carriage was statistically different between outpatients and student volunteers (23.1% vs. 6.7%: p < 0.000). According to a univariate analysis, previous use of antibiotics (ciprofloxacin) appeared to be a risk factor for ESBL carriage (p < 0.05). Escherichia coli was the species most frequently isolated among the ESBL producers in outpatients (66.7%) and student volunteers (90%). Isolates showed additional resistance to gentamicin, ciprofloxacin and trimethoprim/sulfamethoxazole but none of them was resistant to temocillin, amikacin or meropenem. Most of the strains (97%) produced a CTX-M group 1 enzymes [CTX-M-15 (98%) or CTX-M-1 (2%)] and the remaining strains produced SHV-12 enzyme (3%). Conclusions The use of drugs such as amoxicillin, ciprofloxacin and trimethoprim/sulfamethoxazole does not seem appropriate for empirical treatment because of emerging resistance. The implementation in Cameroon or in other African countries of methods of screening ESBL-producing organisms in routine laboratories is of great importance in order for us to offer patients appropriate treatment and for infection control efforts to succeed.